Kepadatan Tanah Timbunan Menggunakan Metode Sand cone Pada Proyek Pembangunan Jalan Lintas Selatan (JLS) Lot 2 Bululawang – Sidomulyo – Tambakrejo - Mahajana, Adam Niestera; Salim, Abdurrosid; Putra, I Nyoman Dita Pahang (Jurnal Talenta Sipil, 2025)
The construction of roads plays a crucial role in supporting public mobility and economic growth. The development of the South Java Road (JLS) is one of the initiatives designed to enhance connectivity in the southern region of Java Island. On the Bululawang – Sidomulyo – Tambakrejo segment, the quality of road construction work is a top priority to ensure safety, durability, and transportation efficiency. The development of JLS is strongly aligned with the Sustainable Development Goals (SDGs), particularly Goal 17, Partnerships for the Goals, involving various parties in ensuring the success of the project. The embankment soil work is a critical aspect, as the compaction of embankment soil directly influences the stability and load-bearing capacity of the road structure. The research methodology started with a literature review, followed by secondary data collection, field observations, and compaction testing using quartz sand and a Speedy Moisture Tester to verify moisture content. The results of the sand cone test at STA 11+725 R, STA 11+750 L, and STA 11+775 R indicate that all points met the minimum compaction criterion of 95%, with field compaction ranging from 97.46% to 98.24% of the maximum dry density (MDD). Although the moisture content at STA 11+725 R was slightly outside the acceptable range, the other points met the allowable moisture content criteria. The testing was conducted in accordance with SNI 03-2828-1992 and SNI 1742-2008, ensuring that the embankment soil compaction quality meets the technical standards.